The Doctrine of Patent Misuse: Origins, Antitrust and the TRIPS Agreement (Journal of Intellectual Property Rights (JIPR), 2024)
Patent misuse refers to the acts of patent owners when they attempt to extend a patent’s exclusivity beyond its physical or temporal scope. Common examples of patent misuse include tying or patent term extension. The patent misuse has its roots in the doctrine of equity and was judicially created doctrine in the United States. Over the past century the concept has evolved considerably and has hanged over the heads of patent owners. However, an antitrust-like analysis is replacing the historical per se illegality of patent misuse acts gradually. The pressure over the concept is slowly taking its toll with increasing calls for its abolition. This paper discusses the history and origins of patent misuse, its interface with competition law and treatment under various articles of the TRIPS Agreement.